The value of multi-slice-computed tomography coronary angiography for risk stratification - van Werkhoven, Jacob M. (Springer-Verlag, 2009)
Multi-slice-computed tomography coronary angiography (CTA) provides direct non-invasive anatomic assessment of the coronary arteries allowing for early identification of coronary artery disease (CAD). This information is useful for diagnosis of CAD, particularly the rule out of CAD. In addition, early identification of CAD with CTA may also be useful for risk stratification. The purpose of this review is to provide an overview of the current literature on the prognostic value of CTA and to discuss how the prognostic information obtained with CTA can be used to further integrate the technique into clinical practice. Non-invasive anatomic assessment of plaque burden, location, composition, and remodeling using CTA may provide prognostically relevant information. This information has been shown to be incremental to the Framingham risk score, coronary artery calcium scoring, and myocardial perfusion imaging. Characterization of atherosclerosis non-invasively has the potential to provide important prognostic information enabling a more patient-tailored approach to disease management. Future studies assessing outcome after CTA-based risk adjustments are needed to further understand the value of detailed non-invasive anatomic imaging.